Zinc Deficiency: Descriptive Epidemiology and Morbidity among Preschool Children in Peri-urban Population in Delhi, India - Dhingra, Usha; Hiremath, Girish; Menon, Venugopal P; Dhingra, Pratibha; Sarkar, Archana; Sazawal, Sunil (Journal of Health, Population and Nutrition, 2009)
Community-based data relating to factors influencing zinc deficiency among preschool children in India are inadequate. Data of a large, double-blinded, randomized, controlled zinc-supplementation trial were used for assessing the descriptive epidemiology of zinc deficiency among children aged 6-35 months (n=940). In total, 609 children were followed up for 120 days for information on morbidity. Of these children, 116 from the control group belonging to the upper and the lower 25th quartile of plasma zinc status at baseline were selected for assessing the association of zinc deficiency with prospective morbidity. At baseline, demographic, socioeconomic and dietary information was collected, and anthropometric measurements and levels of plasma zinc were assessed. At baseline, 73.3% of the children were zinc-deficient (plasma zinc <70 ?g/dL), of which 33.8% had levels of plasma zinc below 60 ?g/dL. A significantly higher risk of morbidity was prevalent among the subjects with lower plasma zinc compared to those with higher levels of plasma zinc. J Health Popul Nutr 2009 Oct; 27(5):632-639